Regulation and Potential Biological Role of Fibroblast Growth Factor 21 in Chronic Kidney Disease - Zhou, Xue; Zhang, Yuefeng; Wang, Ning (Frontiers in Physiology, 2021)
Chronic kidney disease (CKD) is an incurable progressive disease with the progressive impairment of kidney function, which can accelerate the progression of cardiovascular disease, increase the risk of infection, and lead to related complications such as anemia and bone disease. CKD is to a great extent preventable and treatable, and it is particularly important to improve the early diagnosis, strengthen the research underlying the mechanism of disease occurrence and development, and innovate new intervention measures. Fibroblast growth factor 21 (FGF21) belongs to one of members of endocrine FGF subfamily with evolutionarily conserved functions and performs a vital role in the regulation of energy balance and adipose metabolism. FGF21 needs to rely on β-Klotho protein to specifically bind to FGF receptor (FGFR), which activates the FGF21 signaling exerting the biological function. FGF21 is deemed as an important regulatory factor extensively modulating many cellular functions under physiologic and pathologic conditions. Although the metabolic effect of FGF21 has been extensively studied, its potential biological role in the kidney has not been generally investigated. In this review, we summarize the biological characteristics, regulation and biological function of FGF21 based on the current studies, and briefly discuss the potential relationship with chronic kidney disease.